SANCTIFIED SPACES AND SHATTERED SELVES: THE ROLE OF RELIGIOUS SETTINGS IN THE LITERARY UNIVERSE OF INDIRA GOSWAMI - Sarma, Akangkshya; Borah, Mukuta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the complex and multi-dimensional role of religious settings in the literary works of Indira Goswami, with particular focus on her autobiographical text Adha Lekha Dastabez (Goswami, 1988) translated into English as An Unfinished Autobiography (Goswami, 2002) and the novel Neelakanti Braja (Goswami, 1976) translated into English as The Blue Necked God (Goswami, 2013). Goswami, a Jnanpith awardee and a pioneering voice in Indian literature, frequently situates her narratives within sacred geographies that become symbolic terrains of trauma, societal exclusion, spiritual longing, and gendered resistance. Central to this inquiry is the town of Vrindavan, a revered pilgrimage site, which in Goswami's texts emerges as a paradoxical space, simultaneously sacred and deeply oppressive, especially for Hindu widows. Her literary works intricately capture her personal journey from deep psychological anguish and emotional fragmentation to a state of inner resilience and creative empowerment, documenting how she gradually rebuilt her identity and established herself as a distinguished literary figure. The research is anchored in feminist standpoint theory and trauma studies, particularly the frameworks of Cathy Caruth and Patricia Hill Collins. Goswami’s writings are profoundly shaped by her own experiences as a young widow and spiritual seeker, which infuse her portrayals of marginalized women in religious spaces with authenticity and emotional depth. The widows in her narratives are not merely symbolic of suffering or passive victims of patriarchal oppression; rather, they emerge as resilient and complex individuals who assert their agency and fight to reclaim their voices. Religious rituals, temple spaces, and the mythological backdrop of cities like Vrindavan are re-signified in her texts to critique the dominant patriarchal and theological ideologies that structure widowhood in Indian society. By examining how these religious geographies become sites of both confinement and contestation, this paper asserts that Goswami’s narratives offer a profound literary resistance to the institutionalized marginalization of women.